Relative assessment of the microstructure, properties and bioactivity of 3D-printed and rolled Ti6Al4V with micro-arc oxidation (MAO) and hydrothermal (HT) treatment - Zhang, Yingpeng; Luo, Sisi; Zhong, Yuan; Wang, Qun; Ramachandran, Chidambaram Seshadri (Journal of materials research and technology, 2023)
The surface modification of 3D printed Ti6Al4V (3D-Ti64) and rolled Ti6Al4V (RO-Ti64) was carried out using optimized micro-arc oxidation (MAO) and hydrothermal (HT) treatment processes. The results showed that the 3D-Ti64 coating had a typical porous structure that was identical to the phase composition of the RO-Ti64 coating, and both exhibited super hydrophilic properties (contact angle of 0°). It was found that the 3D-Ti64 coating (1.40 × 10−7A/cm2, 39.38 MPa) had greater corrosion current density and adhesion strength compared to the RO-Ti64 coating (0.76 × 10−7A/cm2, 33.69 MPa). In addition, the HAP crystals formed by 3D-Ti64 and RO-Ti64 coatings after being cultured in SBF were not significantly different, indicating that both coatings had comparable in vitro bioactivity. However, the 3D-printed porous Ti64 coating formed a porous structure only around the edges, while the central region had a flocculent structure with unfinished electrolytic oxidation. Moreover, it was found that more HAP crystals were formed in the edge region after HT treatment. In short, the MAO and HT treatment parameters optimized on rolled Ti alloys can be inherited for continued use on 3D-printed Ti alloy solids. However, more considerations may need to be made for the 3D printing of porous Ti alloys.